The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10295-011-1070-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ethanol, citric acid, and α-amylase production from date wastes by strains of Saccharomyces cerevisiae, Aspergillus niger, and Candida guilliermondii

Abstract: The present study deals with submerged ethanol, citric acid, and α-amylase fermentation by Saccharomyces cerevisiae SDB, Aspergillus niger ANSS-B5, and Candida guilliermondii CGL-A10, using date wastes as the basal fermentation medium. The physical and chemical parameters influencing the production of these metabolites were optimized. As for the ethanol production, the optimum yield obtained was 136.00 ± 0.66 g/l under optimum conditions of an incubation period of 72 h, inoculum content of 4% (w/v), sugars con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 25 publications
(41 reference statements)
3
13
1
Order By: Relevance
“…Monga et al (2011) have also reported the use of casein and peptone for the biosynthesis of amylase using various Aspergillus species. Acourene and Ammouche (2012) reported that urea was the most compatible elicitor for biosynthesis of amylase from A. niger which disagrees with the present findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Monga et al (2011) have also reported the use of casein and peptone for the biosynthesis of amylase using various Aspergillus species. Acourene and Ammouche (2012) reported that urea was the most compatible elicitor for biosynthesis of amylase from A. niger which disagrees with the present findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Aspergillus awamori nakazawa was also reported as an effective producer of glucoamylases and proteases in solid state fermentation with wheat bran as substrate (Negi and Banerjee, 2009). Acourene and Ammouche (2012) have produced α-amylase using three fungal strains, Saccharomyces cerevisiae, A. niger , and Candida guilliermondii from date wastes. Roses and Guerra (2009) have optimized production of amylase by A. niger using sugarcane bagasse as the substrate by solid-state fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using bioethanol instead of gasoline leads to the reduction of carbon emission by 80% and overall gasoline consumption by more than 30% (Elsanhoty et al, 2012). The production of bioethanol from lignocellulose raw materials requires generally the incorporation of an efficient pretreatment, followed by a scarification of the carbohydrates to obtain satisfactory effectiveness (Acourene and Ammouche, 2012). Compared to the use of gasoline, bioethanol helps to reduce CO 2 emission to about 80% (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the high level of sugarcane bagasse production after the completion of Khuzestan province projects (three million tons per year) and the problems caused due to its storage require a comprehensive measurement in the direction of its optimized utilization and citric acid production (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%